A concentric umbilical cable for unmanned aerial vehicles and a preparation method thereof
By combining materials such as modified polypropylene and macromolecular voltage stabilizers, the mechanical strength and insulation performance of the UAV umbilical cord cable are improved, and the problems of large weight and poor performance of existing cables are solved, thus achieving lightweight and efficient cables powered by.
Patent Information
- Application Number
- CN202411629335.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The umbilical cord cables of existing drones are heavy and have poor mechanical properties, resulting in interruption of power supply and poor signal transmission, limiting the operating range of the drone.
Modified polypropylene is used to prepare the inner and outer insulation layer. The mechanical strength and insulation performance of the cable are improved by combining macromolecular voltage stabilizers and modified nanotitanium dioxide, and the compatibility and performance of the material are improved by grafting treatment of allylamine. .
The lightweight and high mechanical properties of the cable are achieved, reducing the overall weight of the cable and improving its insulation performance, expanding the operating range of the drone.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of umbilical cables for unmanned aerial vehicles, and in particular to a concentric umbilical cable for unmanned aerial vehicles and a preparation method thereof. Background Art
[0002] The umbilical cable of a drone plays the role of power supply and signal transmission during the high-altitude operation of the drone. However, the existing umbilical cables of drones mostly use ordinary cables, which are heavy and have poor mechanical properties, resulting in power outages or poor signal transmission during the operation, which greatly affects the operation range of the drone. Therefore, in order to avoid this problem, the present application improves the insulation layer of the cable, on the one hand, improves the mechanical strength and insulation performance of the cable, and on the other hand, reduces the weight of the cable, thereby expanding the operation range of the drone.
[0003] When reducing the weight of the cable insulation layer, it is generally adopted to reduce the thickness of the cable insulation layer. However, if the performance of the cable insulation layer is not improved while reducing the thickness, the cable insulation layer after the thickness is reduced will be easy to break or age rapidly during the power supply process. At present, conventional cable insulation layer improvements mostly use small molecule voltage stabilizers for blending or grafting modification, or use some inorganic additives. However, both of them have some problems that are difficult to overcome, such as small molecule voltage stabilizers are easy to migrate out, and inorganic additives are easy to agglomerate during the addition process, resulting in uneven distribution. Therefore, the present application aims at the above two problems, provides a macromolecular voltage stabilizer and modifies the inorganic additives to make their distribution more uniform, thereby improving the overall performance of the cable insulation layer, and the improved cable insulation layer can reduce its thickness and reduce its overall weight due to its good performance. Summary of the invention
[0004] The object of the present invention is to provide a concentric umbilical cable for unmanned aerial vehicles and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a concentric unmanned aerial vehicle umbilical cable, the umbilical cable comprising a cable core, an optical fiber loose tube, a main conductor layer, an inner insulating layer, a spare conductor layer, an outer insulating layer and an outer sheath layer, wherein the inner insulating layer and the outer insulating layer are both prepared by modified polypropylene;
[0007] The modified polypropylene comprises the following preparation steps:
[0008] S1. Weigh polypropylene, macromolecular voltage stabilizer, modified nano titanium dioxide and dicumyl peroxide in a mass ratio of 98: 0.015-0.018: 0.015-0.02: 0.009-0.01 and mix them evenly. Preheat the torque rheometer to 90-100°C, then pour in the above-mentioned materials weighed and mixed evenly in a mass ratio, mix for 5-8 minutes, then heat to 190-210°C, control the speed to 45-55r / min, mix for 9-11 minutes, and take out for use after mixing.
[0009] S2. Preheat the flat vulcanizer to 180-200°C, put the mixed material in S1 into it, preheat for 3-5 minutes, increase the pressure to 5 MPa and maintain the pressure for 4-6 minutes, then increase the pressure to 10 MPa and maintain the pressure for 4-6 minutes, then increase the pressure to 15 MPa and maintain the pressure for 4-6 minutes, then take out the mold with the material, water-cool it to 25-35°C, and obtain modified polypropylene.
[0010] As an optimization, the macromolecular voltage stabilizer includes the following preparation steps: under the condition of a temperature of 0-5°C, adding p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 7-8 times that of p-hydroxyacetophenone and stirring evenly, reacting for 2.2-2.5 hours, adjusting the temperature to 5-15°C, adding a sodium hydroxide solution to adjust the pH to 5.5-6.5, adding 2,2,6,6-tetramethylpiperidinamine with a mass of 1.1-1.2 times that of p-hydroxyacetophenone after the adjustment, adjusting the temperature to 35-45°C, reacting until the pH does not change, adding allylamine with a mass of 0.35-0.45 times that of p-hydroxyacetophenone again, heating to 75-85°C after the addition is complete, reacting for 3.5-4.5 hours, performing reduced pressure filtration, washing the filtered product repeatedly with acetone for 3-5 times, and placing the filter cake in a vacuum drying oven to dry, thereby obtaining a macromolecular voltage stabilizer.
[0011] As an optimization, the cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 7.5 to 8.5 times that of the cyanuric chloride, stirring for 15 to 20 minutes, and mixing evenly.
[0012] As an optimization, the mass fraction of the sodium hydroxide solution is 10% to 15%.
[0013] As an optimization, the modified nano titanium dioxide includes the following preparation steps: adding the pretreated nano titanium dioxide to anhydrous ethanol with a mass of 10 to 12 times the mass of the nano titanium dioxide, ultrasonically dispersing for 10 to 15 minutes, adding (3,3,3-trifluoropropyl)methyldiethoxysilane with a mass of 0.02 to 0.04 times the mass of the nano titanium dioxide, stirring for 10 to 15 minutes at a temperature of 30 to 35°C, and then adding dibutyltin dilaurate, stirring for 4 to 5 hours, cooling to room temperature for aging after the reaction, and then centrifuging, and washing the separated product with anhydrous ethanol and deionized water for 3 to 5 times, and then drying to obtain the modified nano titanium dioxide.
[0014] As an optimization, the nano titanium dioxide pretreatment is to add the nano titanium dioxide into anhydrous ethanol with a mass of 70 to 80 times that of the nano titanium dioxide, soak it for 1 to 1.5 hours, and then filter it. After drying the filtered product at a temperature of 80 to 90° C. for 8 to 10 hours, take it out for use.
[0015] As an optimization, the mass ratio between the dibutyltin dilaurate and nano-titanium dioxide is 1:0.05%~0.1%.
[0016] A concentric umbilical cable for unmanned aerial vehicles, prepared by any of the preparation methods described above
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] This application optimizes the cable insulation layer to reduce the overall weight of the cable and enhance its mechanical properties. In this process, this application innovatively uses a macromolecular voltage stabilizer, effectively avoiding the problem of easy precipitation of traditional small molecule voltage stabilizers. In order to improve the compatibility of the macromolecular voltage stabilizer in polypropylene, this application further grafts it with allylamine.
[0019] In the selection of voltage stabilizers, the present application first selects p-hydroxyacetophenone as the main stabilizer, whose unique keto-enol interconversion structure can absorb and release the energy of high-energy electrons, thereby protecting the polypropylene macromolecule chain. At the same time, the present application introduces hindered amines, which can capture active free radicals generated in the polymer and interrupt the oxidation reaction chain. These two substances are cleverly grafted onto cyanuric chloride to form a close fit between molecules. In addition, allylamine is also grafted onto cyanuric chloride. As a polar compound, it introduces dense deep traps into the material, which can capture the injected charge and form a barrier, effectively inhibiting the further injection of charge.
[0020] In the polymerization process of polypropylene and macromolecular voltage stabilizer, the present application adopts the peroxide crosslinking method, in which dicumyl peroxide is used as an initiator, which decomposes under high temperature and high pressure conditions to produce active free radicals, promoting the crosslinking reaction between polypropylene molecules. At the same time, these free radicals can also open the double bonds in the graftable compound and graft it onto the polypropylene macromolecular chain through a free radical addition reaction, realizing the chain termination process.
[0021] In order to further improve the performance of the material, the present application also adds nano titanium dioxide as an inorganic additive. Titanium dioxide not only has antioxidant properties, but also improves the thermal conductivity of the material. However, due to the poor dispersibility of inorganic materials, the present application pre-modifies them with a silane coupling agent (especially fluorinated silane) to improve their dispersibility and improve the hydrophobic properties of the polypropylene surface. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] S1. At a temperature of 0°C, add p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 7 times that of p-hydroxyacetophenone, stir evenly, react for 2.2 hours, adjust the temperature to 5°C, add sodium hydroxide solution to adjust the pH to 5.5, add 2,2,6,6-tetramethylpiperidinamine with a mass of 1.1 times that of p-hydroxyacetophenone after adjustment, adjust the temperature to 35°C, react until the pH does not change, then drop allylamine with a mass of 0.35 times that of p-hydroxyacetophenone again, raise the temperature to 75°C after the dropwise addition, react for 3.5 hours, filter under reduced pressure, wash the filtered product with acetone repeatedly for 3 times, and place the filter cake in a vacuum drying oven to dry, thereby obtaining a macromolecular voltage stabilizer; wherein the cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 7.5 times that of cyanuric chloride, stirring for 15 minutes, and mixing evenly; wherein the mass fraction of the sodium hydroxide solution is 10%;
[0025] S2, adding the pretreated nano titanium dioxide to anhydrous ethanol with a mass of 10 times that of the nano titanium dioxide, ultrasonically dispersing for 10 minutes, adding (3,3,3-trifluoropropyl)methyldiethoxysilane with a mass of 0.02 times that of the nano titanium dioxide, stirring for 10 minutes at a temperature of 30°C, and then adding dibutyltin dilaurate, stirring and reacting for 4 hours, cooling to room temperature after the reaction, aging, and then centrifuging, and washing the separated product with anhydrous ethanol and deionized water for 3 times, and then drying to obtain modified nano titanium dioxide; wherein, the nano titanium dioxide pretreatment is to add the nano titanium dioxide to anhydrous ethanol with a mass of 70 times that of the nano titanium dioxide, soaking for 1 hour, and then filtering, and the filtered product is dried at a temperature of 80°C for 8 hours, and then taken out for use; the mass ratio between dibutyltin dilaurate and nano titanium dioxide is 1:0.05%;
[0026] S3, weigh polypropylene, macromolecular voltage stabilizer, modified nano titanium dioxide and dicumyl peroxide in a mass ratio of 98:0.015:0.015:0.009 and mix them evenly, preheat the torque rheometer to 90°C, then pour the above-mentioned materials weighed and mixed evenly in the mass ratio, mix for 5in, then heat to 190°C, control the speed to 45r / min, mix for 9min, and take out for use after mixing;
[0027] S4. Preheat the flat vulcanizer to 180°C, put the mixed material in S1 into it, preheat for 3 minutes, increase the pressure to 5 MPa and maintain the pressure for 4 minutes, then increase the pressure to 10 MPa and maintain the pressure for 4 minutes, then increase the pressure to 15 MPa and maintain the pressure for 4 minutes, then take out the mold with the material, water cool it to 25°C, and obtain modified polypropylene.
[0028] Example 2
[0029] S1. At a temperature of 3°C, add p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 7.5 times that of p-hydroxyacetophenone and stir evenly. After reacting for 2.4 hours, adjust the temperature to 10°C, add sodium hydroxide solution to adjust the pH to 6, add 2,2,6,6-tetramethylpiperidinamine with a mass of 1.15 times that of p-hydroxyacetophenone after adjustment, adjust the temperature to 40°C, react until the pH does not change, then drop allylamine with a mass of 0.4 times that of p-hydroxyacetophenone again, raise the temperature to 80°C after the dropwise addition, react for 4 hours, filter under reduced pressure, wash the filtered product with acetone repeatedly 4 times, and place the filter cake in a vacuum drying oven to dry, thereby obtaining a macromolecular voltage stabilizer; wherein the cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 8 times that of cyanuric chloride, stirring for 18 minutes, and mixing evenly; wherein the mass fraction of the sodium hydroxide solution is 13%;
[0030] S2, adding the pretreated nano titanium dioxide to anhydrous ethanol with a mass of 11 times that of the nano titanium dioxide, ultrasonically dispersing for 12 minutes, adding (3,3,3-trifluoropropyl)methyldiethoxysilane with a mass of 0.03 times that of the nano titanium dioxide, stirring for 12 minutes at a temperature of 35°C, and then adding dibutyltin dilaurate, stirring and reacting for 4.5 hours. After the reaction is completed, cooling to room temperature for aging, and then centrifugal separation, and washing the separated product with anhydrous ethanol and deionized water for 4 times, and then drying to obtain modified nano titanium dioxide; wherein, the nano titanium dioxide pretreatment is to add the nano titanium dioxide to anhydrous ethanol with a mass of 75 times that of the nano titanium dioxide, soaking for 1.2 hours, and then filtering, and the filtered product is dried at a temperature of 85°C for 9 hours, and then taken out for use; the mass ratio between dibutyltin dilaurate and nano titanium dioxide is 1:0.07%;
[0031] S3, weigh polypropylene, macromolecular voltage stabilizer, modified nano titanium dioxide and dicumyl peroxide in a mass ratio of 98:0.016:0.018:0.0095 and mix them evenly, preheat the torque rheometer to 95°C, then pour in the above materials weighed and mixed evenly, mix for 5-8 minutes, then heat to 200°C, control the speed to 50r / min, mix for 10 minutes, and take out for use after mixing;
[0032] S4. Preheat the flat vulcanizer to 190°C, put the mixed material in S1 into it, preheat for 4 minutes, increase the pressure to 5 MPa and maintain the pressure for 5 minutes, then increase the pressure to 10 MPa and maintain the pressure for 5 minutes, then increase the pressure to 15 MPa and maintain the pressure for 5 minutes, then take out the mold with the material, water cool it to 30°C, and obtain modified polypropylene.
[0033] Example 3
[0034] S1. At a temperature of 5°C, add p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 8 times that of p-hydroxyacetophenone, stir evenly, react for 2.5 hours, adjust the temperature to 15°C, add sodium hydroxide solution to adjust the pH to 6.5, add 2,2,6,6-tetramethylpiperidinamine with a mass of 1.2 times that of p-hydroxyacetophenone after adjustment, adjust the temperature to 45°C, react until the pH does not change, then drop allylamine with a mass of 0.45 times that of p-hydroxyacetophenone again, raise the temperature to 85°C after the addition is complete, react for 4.5 hours, filter under reduced pressure, wash the filtered product with acetone repeatedly for 5 times, and place the filter cake in a vacuum drying oven to dry, so as to obtain a macromolecular voltage stabilizer; wherein the cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 8.5 times that of cyanuric chloride, stirring for 20 minutes, and mixing evenly; wherein the mass fraction of the sodium hydroxide solution is 15%;
[0035] S2, adding the pretreated nano titanium dioxide to anhydrous ethanol with a mass of 12 times that of the nano titanium dioxide, ultrasonically dispersing for 15 minutes, adding (3,3,3-trifluoropropyl)methyldiethoxysilane with a mass of 0.04 times that of the nano titanium dioxide, stirring for 15 minutes at a temperature of 35°C, and then adding dibutyltin dilaurate, stirring and reacting for 5 hours, cooling to room temperature for aging after the reaction, and then centrifuging, and washing the separated product with anhydrous ethanol and deionized water for 5 times, and then drying to obtain modified nano titanium dioxide; wherein, the nano titanium dioxide pretreatment is to add the nano titanium dioxide to anhydrous ethanol with a mass of 80 times that of the nano titanium dioxide, soaking for 1.5 hours, and then filtering, and the filtered product is dried at a temperature of 90°C for 10 hours, and then taken out for use; the mass ratio between dibutyltin dilaurate and nano titanium dioxide is 1:0.1%;
[0036] S3, weigh polypropylene, macromolecular voltage stabilizer, modified nano titanium dioxide and dicumyl peroxide in a mass ratio of 98:0.018:0.02:0.01 and mix them evenly, preheat the torque rheometer to 100°C, then pour the above materials weighed and mixed evenly in the mass ratio, mix for 8 minutes, then heat to 210°C, control the speed to 55r / min, mix for 11 minutes, and take out for use after mixing;
[0037] S4. Preheat the flat vulcanizer to 200°C, put the mixed material in S1 into it, preheat for 3-5 minutes, increase the pressure to 5 MPa and maintain the pressure for 6 minutes, then increase the pressure to 10 MPa and maintain the pressure for 6 minutes, then increase the pressure to 15 MPa and maintain the pressure for 6 minutes, then take out the mold with the material, water-cool it to 35°C, and obtain modified polypropylene.
[0038] Example 4
[0039] The only difference from Example 2 is that in step S1, only p-hydroxyacetophenone is grafted; the details are as follows;
[0040] S1. At a temperature of 3°C, add p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 7.5 times that of p-hydroxyacetophenone, stir evenly, react for 2.4 hours, filter under reduced pressure, wash the filtered product with acetone repeatedly for 4 times, and then dry the filter cake in a vacuum drying oven to obtain a macromolecular voltage stabilizer; wherein the cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 8 times that of cyanuric chloride, stirring for 18 minutes, and mixing evenly.
[0041] Example 5
[0042] The only difference from Example 2 is that p-allylamine is not grafted in step S1; the details are as follows;
[0043] S1. At a temperature of 3°C, add p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 7.5 times that of p-hydroxyacetophenone, stir evenly, react for 2.4 hours, adjust the temperature to 10°C, add sodium hydroxide solution to adjust the pH to 6, add 2,2,6,6-tetramethylpiperidinamine with a mass of 1.15 times that of p-hydroxyacetophenone after adjustment, adjust the temperature to 40°C, react until the pH does not change, filter under reduced pressure, wash the filtered product with acetone repeatedly for 4 times, and place the filter cake in a vacuum drying oven to dry, so as to obtain a macromolecular voltage stabilizer; wherein the cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 8 times that of cyanuric chloride, stirring for 18 minutes, and mixing evenly; wherein the mass fraction of the sodium hydroxide solution is 13%.
[0044] Example 6
[0045] The only difference from Example 2 is that modified nano titanium dioxide is not added in step S3; the details are as follows;
[0046] S3. Weigh polypropylene, macromolecular voltage stabilizer and diisopropylbenzene peroxide in a mass ratio of 98:0.016:0.0095 and mix them evenly. Preheat the torque rheometer to 95°C, then pour in the above-mentioned materials weighed and mixed evenly, mix for 5-8 minutes, then raise the temperature to 200°C, control the speed to 50r / min, mix for 10 minutes, and take out for use after mixing.
[0047] Example 7
[0048] The only difference from Example 2 is that no macromolecular voltage stabilizer is added in step S3; the details are as follows;
[0049] S3. Weigh polypropylene and modified nano titanium dioxide in a mass ratio of 98:0.018 and mix them evenly. Preheat the torque rheometer to 95°C, then pour in the above-mentioned materials weighed in a mass ratio and mixed evenly, mix for 5-8 minutes, then raise the temperature to 200°C, control the speed to 50r / min, mix for 10 minutes, and take out for use after mixing.
[0050] Example 8
[0051] The only difference from Example 2 is that nano titanium dioxide is added in step S3; the details are as follows;
[0052] S3. Weigh polypropylene, macromolecular voltage stabilizer, nano titanium dioxide and diisopropylbenzene peroxide in a mass ratio of 98:0.016:0.018:0.0095 and mix them evenly. Preheat the torque rheometer to 95°C, then pour in the above-mentioned materials weighed in the mass ratio and mixed evenly, mix for 5-8 minutes, then raise the temperature to 200°C, control the speed to 50r / min, mix for 10 minutes, and take out for use after mixing.
[0053] Test Example 1
[0054] The modified polypropylene prepared in Examples 1 to 8 was prepared into dumbbell-shaped specimens with a thickness of 1 mm. The mechanical properties of the specimens were tested according to GB / T1040.1-2018 standard. The tensile rate was set to 100 mm / min. The test experimental data are as follows:
[0055] Table 1 Mechanical properties experimental data
[0056]
[0057] From the comparison of the experimental data in Table 1, it can be found that the tensile strength and elongation at break in Examples 1 to 3 are the best, showing good mechanical properties; in Example 4, only p-hydroxyacetophenone is grafted, resulting in the inability to graft with polypropylene in the end. Although the macromolecular voltage stabilizer is not easy to precipitate, its non-grafting will lead to a decrease in the overall mechanical properties; and Example 5 is the same as Example 4, both of which are caused by not being polymerized with polypropylene;
[0058] In Example 6, due to its unmodified nano-titanium dioxide, although the mechanical properties decreased, the decrease was not much. In Example 7, no macromolecular voltage stabilizer was added, resulting in a decrease in the final mechanical properties. The main reason may be that diisopropylbenzene peroxide was not added to promote polymerization, resulting in a poor final polymerization degree. In Example 8, unmodified nano-titanium dioxide was used, resulting in the largest decrease in mechanical properties. This should be because the unmodified nano-titanium dioxide agglomerates, resulting in a decrease in overall performance.
[0059] Test Example 2
[0060] The modified polypropylene prepared in Examples 1 to 8 was prepared into samples with a thickness of 40±5μm, and each sample was tested 10 times. The experiment used ball-plate electrodes, and the test object was placed between the electrodes and completely immersed in silicone oil. The test was carried out at room temperature, the voltage increase rate was set to 500V / s, and the voltage was gradually increased in a linear manner until the test object broke down, at which time the breakdown voltage value was recorded;
[0061] Table 2 DC breakdown strength test results
[0062]
[0063] From the comparison of experimental data in Table 2, it can be found that the DC breakdown strength in Examples 1 to 3 is the highest, so when the insulating layer is prepared later, the insulation thickness can be effectively reduced; in Examples 4 and 5, only the grafting of p-hydroxyacetophenone is compared with the simultaneous grafting of hindered amine and p-hydroxyacetophenone, although the improvement effect is there, it is still slightly less than the synergistic cooperation of the two; although the change of titanium dioxide in Examples 6 and 8 will lead to a decrease, the decrease is still within expectations, and the addition of inorganic substances may only play an auxiliary role; Example 7 is the expected lowest point, because at this time no voltage stabilizer is added, and the improvement of the DC breakdown strength by titanium dioxide alone is still negligible.
[0064] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a concentric umbilical cable for a drone, characterized in that: The umbilical cable comprises a cable core, an optical fiber loose tube, a main conductor layer, an inner insulating layer, a spare conductor layer, an outer insulating layer and an outer sheath layer, wherein the inner insulating layer and the outer insulating layer are both made of modified polypropylene; The modified polypropylene comprises the following preparation steps: S1. Weigh polypropylene, macromolecular voltage stabilizer, modified nano titanium dioxide and dicumyl peroxide in a mass ratio of 98: 0.015-0.018: 0.015-0.02: 0.009-0.01 and mix them evenly. Preheat the torque rheometer to 90-100°C, then pour in the above-mentioned materials weighed and mixed evenly in a mass ratio, mix for 5-8 minutes, then heat to 190-210°C, control the speed to 45-55r / min, mix for 9-11 minutes, and take out for use after mixing. S2, preheat the flat vulcanizer to 180-200°C, put the mixed materials in S1 into the press, preheat for 3-5 minutes, increase the pressure to 5 MPa and maintain the pressure for 4-6 minutes, then increase the pressure to 10 MPa and maintain the pressure for 4-6 minutes, then increase the pressure to 15 MPa and maintain the pressure for 4-6 minutes, then take out the mold with the materials, water cool to 25-35°C, and obtain modified polypropylene; The macromolecular voltage stabilizer comprises the following preparation steps: under the condition of temperature of 0-5°C, adding p-hydroxyacetophenone to a cyanuric chloride solution with a mass of 7-8 times that of p-hydroxyacetophenone, stirring evenly, reacting for 2.2-2.5h, adjusting the temperature to 5-15°C, adding a sodium hydroxide solution to adjust the pH to 5.5-6.5, adding 2,2,6,6-tetramethylpiperidinamine with a mass of 1.1-1.2 times that of p-hydroxyacetophenone after adjustment, adjusting the temperature to 35-45°C, reacting until the pH does not change, adding allylamine with a mass of 0.35-0.45 times that of p-hydroxyacetophenone again, heating to 75-85°C after the addition is complete, reacting for 3.5-4.5h, performing vacuum filtration, washing the filtered product with acetone repeatedly for 3-5 times, and placing the filter cake in a vacuum drying oven for drying, so as to obtain the macromolecular voltage stabilizer.
2. The method for preparing a concentric UAV umbilical cable according to claim 1, characterized in that: The cyanuric chloride solution is prepared by adding cyanuric chloride to acetone with a mass of 7.5 to 8.5 times that of the cyanuric chloride, stirring for 15 to 20 minutes, and mixing uniformly.
3. The method for preparing a concentric UAV umbilical cable according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution is 10% to 15%.
4. The method for preparing a concentric UAV umbilical cable according to claim 1, characterized in that: The modified nano titanium dioxide comprises the following preparation steps: adding the pretreated nano titanium dioxide to anhydrous ethanol with a mass of 10 to 12 times the mass of the nano titanium dioxide, ultrasonically dispersing for 10 to 15 minutes, adding (3,3,3-trifluoropropyl)methyldiethoxysilane with a mass of 0.02 to 0.04 times the mass of the nano titanium dioxide, stirring for 10 to 15 minutes at a temperature of 30 to 35°C, adding dibutyltin dilaurate, stirring for reaction for 4 to 5 hours, cooling to room temperature for aging after the reaction is completed, and then centrifugally separating, and washing the separated product with anhydrous ethanol and deionized water for 3 to 5 times, and then drying to obtain the modified nano titanium dioxide.
5. The method for preparing the concentric UAV umbilical cable according to claim 4, characterized in that: The nano titanium dioxide pretreatment is to add the nano titanium dioxide into anhydrous ethanol with a mass of 70 to 80 times the mass of the nano titanium dioxide, soak it for 1 to 1.5 hours, then filter it, dry the filtered product at a temperature of 80 to 90° C. for 8 to 10 hours, and then take it out for use.
6. A concentric umbilical cable for drones, characterized in that: The method is prepared according to any one of claims 1 to 5.
Citation Information
Patent Citations
Light aging resistant polypropylene composition and preparation method thereof
CN101759922A
Environment-friendly transparent cable sheathing material
CN106317803A